Bike sharing systems. - (:unkn) unknown (My University, 2012)
Bike rental systems offer new mobility options for spontaneous day-to-day travel, for commuters in city centres and peripheral employment centres, and for leisure cycling in the city and the region. An increased integration of bike rental services into local public transport will provide the missing link in transport networks. (Difu)
Keywords: Individualverkehr; Fahrradverkehr; Öffentliches Fahrradverleihsystem; Fahrradverleih; Bike Sharing; Fahrradnutzung; Fahrradbenutzung